Development and evaluation of a novel floating in situ gelling system of amoxicillin for eradication of Helicobacter pylori - Rajinikanth P.S.; Balasubramaniam J.; Mishra B. (My University, 2025)
The aim of this study was to develop a new intra-gastric floating in situ gelling system for controlled delivery of amoxicillin for the treatment of peptic ulcer disease caused by Helicobacter pylori (H. pylori). Gellan based amoxicillin floating in situ gelling systems (AFIG) were prepared by dissolving varying concentrations of gellan gum in deionized water containing sodium citrate, to which varying concentrations of drug and calcium carbonate, as gas-forming agent, was added and dissolved by stirring. The formulation variables like concentration of gellan gum and calcium carbonate significantly affected the in vitro drug release from the prepared AFIG. The in vivo H. pylori clearance efficacy of prepared AFIG in reference to amoxicillin suspension following repeated oral administration to H. pylori infected Mongolian gerbils was examined by polymerase chain reaction (PCR) technique and by a microbial culture method. AFIG showed a significant anti-H. pylori effect in the in vivo gerbil model. It was noted that the required amount of amoxicillin for eradication of H. pylori was 10 times less in AFIG than from the corresponding amoxicillin suspension. The results further substantiated that the prepared AFIG has feasibility of forming rigid gels in the gastric environment and eradicated H. pylori from the gastrointestinal tract more effectively than amoxicillin suspension because of the prolonged gastrointestinal residence time of the formulation. © 2006 Elsevier B.V. All rights reserved.